1975
DOI: 10.1063/1.431300
|View full text |Cite
|
Sign up to set email alerts
|

Internal rotation in ethylamine: A treatment as a two-top problem

Abstract: The infrared absorption spectra of eight isotopic ethylamine molecules, i.e., CH3CH2NH2, CD3CH2NH2, CH3CD2NH2, CD3CD2NH2, CH3CH2ND2, CD3CJ2ND2, CH3CD2ND2, and CD3CD2ND2, have been examined in the vapor phase in the 300–100 cm−1 region. Several Q-branch peaks were observed for each isotopic species and assigned to the torsional oscillations of the methyl and amino groups of the trans and gauche isomers. The energy levels were calculated on the basis of a coupled two-top system. The analysis yielded a probable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 8 publications
4
23
0
Order By: Relevance
“…This value was in agreement with earlier determined values of 107 ± 70 cm –1 (1.28 ± 0.84 kJ/mol) from electron diffraction study, 110 ± 50 cm –1 (1.32 ± 0.60 kJ/mol) from a microwave investigation, and 100 ± 10 cm –1 (1.20 ± 0.12 kJ/mol) from an infrared study of ethylamine in an argon matrix . However, several of the earlier studies reported the gauche conformer as the more stable form, and it is rather interesting that second‐order Møller–Plesset (MP2, full)/6‐311+G(2d,2p) calculations predict the gauche conformer to be the more stable form by 66 cm –1 (0.79 kJ/mol). However, without the diffuse functions the trans form is predicted to be the more stable conformer by 32 cm –1 (0.38 kJ/mol).…”
Section: Introductionsupporting
confidence: 91%
“…This value was in agreement with earlier determined values of 107 ± 70 cm –1 (1.28 ± 0.84 kJ/mol) from electron diffraction study, 110 ± 50 cm –1 (1.32 ± 0.60 kJ/mol) from a microwave investigation, and 100 ± 10 cm –1 (1.20 ± 0.12 kJ/mol) from an infrared study of ethylamine in an argon matrix . However, several of the earlier studies reported the gauche conformer as the more stable form, and it is rather interesting that second‐order Møller–Plesset (MP2, full)/6‐311+G(2d,2p) calculations predict the gauche conformer to be the more stable form by 66 cm –1 (0.79 kJ/mol). However, without the diffuse functions the trans form is predicted to be the more stable conformer by 32 cm –1 (0.38 kJ/mol).…”
Section: Introductionsupporting
confidence: 91%
“…However, the same group shortly after that concluded 51 that the trans conformation was in fact more stable by 0.66 kcal/mol. This molecule, for all of its apparent simplicity, is complicated by the fact that the rotational barrier is rather low, as is the inversion barrier for the amino group, and those two motions are coupled.…”
Section: Ethylaminementioning
confidence: 87%
“…Durig and Li 30b reached substantially the same conclusion independently from a study of the infrared spectrum (trans stable by 0.59 kcal/mol). Additionally, these authors concluded that the rotational barrier of the methyl group for the gauche form is 3.71 6 0.5 kcal/mol, while Tsuboi et al 51 report that the trans methyl barrier has a height of 3.74 kcal/mol, and the gauche is 3.56 kcal/mol. Durig also reports the gauche barrier for the N,N-dideutero compound has a height of 3.59 kcal/mol, and in agreement with that obtained by microwave studies, 3.57 kcal/mol (the microwave studies are cited as unpublished).…”
Section: Ethylaminementioning
confidence: 96%
“…This value was in agreement with earlier determined values of 107 ± 70 cm À1 (1.28 ± 0.84 kJ/mol) from electron diffraction study [2], 110 ± 50 cm À1 (1.32 ± 0.60 kJ/mol) from a microwave investigation [3], and 100 ± 10 cm À1 (1.20 ± 0.12 kJ/mol) from an infrared study of ethylamine in an argon matrix [4]. However, several of the earlier studies [5][6][7][8] reported the gauche conformer as the more stable form, and it is rather interesting that MP2(full)/6-311 + G(2d,2p) calculations predict [1] the gauche conformer to be the more stable form by 66 cm À1 (0.79 kJ/mol). However, without the diffuse functions the trans form is predicted to be the more stable conformer by 32 cm À1 (0.38 kJ/mol).…”
Section: Introductionmentioning
confidence: 99%